2016
DOI: 10.1186/s13000-016-0463-9
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and detection method evaluation of group B streptococcus from prenatal vaginal specimen in Northwest China

Abstract: Sensitive and efficient detection of Group B Streptococcus (GBS) colonization in pregnant women is essential for prescription of prophylaxis at the time of delivery as GBS is an opportunistic pathogen known to cause infant mortality. In this report, two studies were conducted on the methods of GBS detection in Shaanxi province, China, a region lacking data for GBS detection and occurrence. For Study 1, 100 GBS culture-positive vaginal swabs were collected from 1,567 pregnant women for evaluation by direct late… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Overall, the incidence of GBS infection ranges from 0.17 to 3.06 cases per 1000 LB in low-income and middle-income countries,18 and the mortality rate is higher than in developed countries (10%–60% compared with 7%–11%) 19. In Europe the incidence is 0.5–2 cases per 1000 LB, with a mortality rate of 4%–10% 3…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the incidence of GBS infection ranges from 0.17 to 3.06 cases per 1000 LB in low-income and middle-income countries,18 and the mortality rate is higher than in developed countries (10%–60% compared with 7%–11%) 19. In Europe the incidence is 0.5–2 cases per 1000 LB, with a mortality rate of 4%–10% 3…”
Section: Introductionmentioning
confidence: 99%
“…This method is shown to have comparable or even better sensitivity and specificity than standard Lim broth enrichment followed by blood agar cultures [17,27]. Using the carrot broth method, many studies have shown a prevalence of GBS in vaginal swabs in the range of 5-19.8 % in pregnant women [8,17,28]. In India, the prevalence of GBS is highly variable depending on the population studied or the methods used.…”
Section: Discussionmentioning
confidence: 99%
“…This method is shown to have a sensitivity and specificity comparable or even better than the standard Lim broth enrichment followed by blood agar cultures (Block et al, 2008, Church et al, 2008. Using the Carrot Broth method, many studies have shown the prevalence of GBS in vaginal swabs in the range of 5 to 19.8% in pregnant women (Choi et al, 2021, Church et al, 2008, Xie et al, 2016. In India, the prevalence of GBS is highly variable depending on the population studied or the methods used.…”
Section: Discussionmentioning
confidence: 99%
“…GBS culture is normally performed on 5% Sheep Blood Agar (SBA) and colonies are detected by the breakdown of red blood cells that produce a characteristic zone of haemolysis. A confirmatory test for GBS is the Christie Atkins Munch Peterson (CAMP) test, or serotyping via an agglutinin reaction on selected β-haemolytic colonies (Rashwan, 2020, Xie et al, 2016. As an alternative to Blood agar, Crome agar is also used to detect GBS.…”
Section: Introductionmentioning
confidence: 99%